The Symbolic Meaning of the Cimbingan Tradition in the Chinese Ethnic Community in Turirejo Village, Lawang District, Malang Regency - Rengganis Aurellia Fika Lewenussa; Nur Hadi (Faculty of Social Science, Universitas Negeri Malang, 2024)
This research describes the Cimbingan tradition which is carried out once a year by visiting thegraves of ancestors and cleaning and decorating the graves. Ethnic Chinese still strongly holdthe belief to always honor ancestors, so this tradition is still carried out to this day. This researchaims to reveal three important focuses, namely: the function and meaning of each equipmentused, the worship procession of the Cimbingan tradition, and the symbolic meaning in theCimbingan tradition. The method used in this research is qualitative descriptif. This research usesdata collection techniques in the form of observation, in-depth interviews, and documentation withprimary data sources and secondary data sources. Based on the research, it can be concludedthat there is a meaning contained in each equipment used such as the meaning of candles andincense which means as a light for the ancestors in the afterlife, besides the offerings of food anddrinks which means a form of attention from children to parents. Furthermore, afterlife money andduplicate items made of paper which means a form of fulfilling the needs of ancestors in theafterlife. Furthermore, the five-color paper means a form of description of the ancestors' homesin the afterlife. In addition, there are three stages in the procession of the Cimbingan traditionwhere there is a preparation stage, a prayer stage, and a closing stage. The meaning in thistradition is a form of filial piety of children to parents, where children still remember and showattention to parents even though parents are gone.